Penerapan Pembelajaran International Class Program (ICP) dalam Peningkatan Kompetensi Siswa di MTs Salafiyah Syafi'iyah Tebuireng Jombang - Mustofa, Ali (Didaktika Religia, 2015)
The research is intended to examine the implementation of ICP (International Class Program) at MTs Salafiyah Syafiâ€™iyah Tebuireng Jombang.This study was descriptive. The data were gained from observation, interviews, and documentaion. The result of the study revealed the following findings. Firstly, the teachear planned educational calender, lesson plan, attendence list, a list of scores, daily test analysis, and remidial and as well as enrichment Â materials, modul or work book which is designed in accordance with indicator ofÂ  UN SKL and PSL. Secondly, the main material used by teachers is work book designed and based on national syllabus and Cambridge curriculum. Thirdly, the students use work book, mastery learning, ABL, and practising foreign languages (Arabic and English) both in and outside the classroom. Fourthly, there are three elements in evaluating students: cognitive competence based on dialy discussion, middle, final, national test and cambridge examination; affective value based on the students seriousness or interest in the subjects, their behaviour and attitude both inside and outside the classroom, the students psychomotor based on practising the subjects. Finally, the competencesÂ  expected are that the students national examantion score is above of 8.5, they are able to speak foreign languages actively; the students become champion in contests at the provincial level; the students have great achievement in arts, culture, and religion such as: mathematics olympic champion, Islamic studies, and many others